Universities, Regional Development and Economic Competitiveness: the Polish Case - Kwiek, Marek (My University, 2012)
This paper explores the regional engagement of Polish universities and shows that the assumptions about the linkages between universities, their regions and economic competitiveness that are taken for granted in the knowledgeeconomy policy discourse in advanced Western European economies may not fit Poland today. Universities in Poland contribute to economic development,but numerous other features that are known to contribute to economic growth are non-existent and numerous inhibitors of economic growth, already addressed in knowledge-intensive economies, are still in operation. Two decades of social and economic transformation (often referred to as “catching up with the West,” or “post-communist transition” and “EU accession” periods) are not long enough to bridge the gap between the two parts of Europe, and convergence processes between Poland and Western European economies may last much longer than was initially assumed following the collapse of communism in 1989
Keywords: Poland; Polish higher education; Polish universities; regional mission; regional engagement; third mission; third mission activities; economic competitiveness; public policy; reforms; transition; postcommunist; reforming higher education; Eastern Europe; Central Europe; East/West divide; economic growth; regions; regional development; regional impact; regional role